1.0 management in a 2.0 world: Colleges between the rock and the hard place. Issue 11 (25th June 2018) - Chu, Don
Abstract : If your departments are doing great, then perhaps you don't need to read this. You can just keep doing the same things to get the same results. But if you're like most leaders whose colleges have been stuck for years between "the rock and the hard place, " between growing needs and insufficient resources, then maybe you need to do things differently to get a better result. If you're still reading this, you probably believe in the power of higher education to transform lives and make our world better. Chances are you also believe in yourself, and you feel responsible to make your college and departments better. And if it takes doing things differently to get a better result, so be it.